Genotypic and Phenotypic Characterization of Antimicrobial Resistance Profiles in Non-typhoidal Salmonella enterica Strains Isolated From Cambodian Informal Markets - Schwan, Carla L.; Lomonaco, Sara; Bastos, Leonardo M.; Cook, Peter W.; Maher, Joshua; Trinetta, Valentina; Bhullar, Manreet; Phebus, Randall K.; Gragg, Sara; Kastner, Justin; Vipham, Jessie L. (Frontiers in Microbiology, 2021)
Non-typhoidal Salmonella enterica is a pathogen of global importance, particularly in low and middle-income countries (LMICs). The presence of antimicrobial resistant (AMR) strains in market environments poses a serious health threat to consumers. In this study we identified and characterized the genotypic and phenotypic AMR profiles of 81 environmental S. enterica strains isolated from samples from informal markets in Cambodia in 2018-2019. AMR genotypes were retrieved from the NCBI Pathogen Detection website (https://www.ncbi.nlm.nih.gov/pathogens/) and using ResFinder (https://cge.cbs.dtu.dk/services/). Salmonella pathogenicity islands (SPIs) were identified with SPIFinder (https://cge.cbs.dtu.dk/services/). Susceptibility testing was performed by broth microdilution according to the Clinical and Laboratory Standards Institute (CLSI) standard guidelines M100-S22 using the National Antimicrobial Resistance Monitoring System (NARMS) Sensititre Gram Negative plate. A total of 17 unique AMR genes were detected in 53% (43/81) of the isolates, including those encoding tetracycline, beta-lactam, sulfonamide, quinolone, aminoglycoside, phenicol, and trimethoprim resistance. A total of 10 SPIs (SPI-1, 3-5, 8, 9, 12-14, and centisome 63 [C63PI]) were detected in 59 isolates. C63PI, an iron transport system in SPI-1, was observed in 56% of the isolates (n=46). SPI-1, SPI-4 and SPI-9 were present in 13%, 2%, and 5% of the isolates, respectively. The most common phenotypic resistances were observed to tetracycline (47%; n=38), ampicillin (37%; n=30), streptomycin (20%; n=16), chloramphenicol (17%; n=14), and trimethoprim-sulfamethoxazole (16%; n=13). This study contributes to understanding the AMR genes present in S. enterica isolates from informal markets in Cambodia, as well as support domestic epidemiological investigations of multidrug resistance (MDR) profiles.